2021
DOI: 10.1186/s13568-021-01197-6
|View full text |Cite
|
Sign up to set email alerts
|

F. prausnitzii and its supernatant increase SCFAs-producing bacteria to restore gut dysbiosis in TNBS-induced colitis

Abstract: An increasing number of studies have shown that Faecalibacterium prausnitzii (F. prausnitzii) is a promising anti-inflammatory bacterium that colonizes in the gut and that gut microbiota dysbiosis plays an important role in the pathogenesis of inflammatory bowel disease (IBD). In this study, we report the gut microbiota profile of 2,4,6-trinitrobenzenesulfonic acid (TNBS)-induced colitis mice treated with F. prausnitzii and its supernatant on the basis of high-throughput sequencing. We interestingly found that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Consistent with our previous studies [ 17 20 ], we found that DSS-triggered acute and chronic colitis were similar in terms of disease activity, colon shortening and histopathological changes in the colon, but differed remarkably in terms of gut microbiota profiles. Given that the initiation and progression of UC centers heavily on gut microbiota proportions, the therapeutic potential of fecal microbiota transplantation is increasingly being assessed in UC animal models.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our previous studies [ 17 20 ], we found that DSS-triggered acute and chronic colitis were similar in terms of disease activity, colon shortening and histopathological changes in the colon, but differed remarkably in terms of gut microbiota profiles. Given that the initiation and progression of UC centers heavily on gut microbiota proportions, the therapeutic potential of fecal microbiota transplantation is increasingly being assessed in UC animal models.…”
Section: Introductionsupporting
confidence: 92%
“…DSS and 2,4,6-trinitro-benzenesulfonic acid (TNBS) are established agents for inducing acute and chronic colitis [ 17 20 ]. In this preliminary study, we found that administration of 3 and 2.5% DSS via drinking water can respectively induce acute and chronic colitis in mice while ensuring their survival.…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs, such as butyric acid, acetic acid, and propionic acid, are reported to participate in controlling inflammation and repair the colon epithelium [32]. SCFA levels are known to be reduced in fecal samples of IBD patients and in experimental colitis [44][45][46]. Saffron preserved the essential SCFAs in mice feces, indicating its beneficial attributes in maintaining colonic microbial populations during colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus clausii is reported to control the development of Clostridium difficile infection in clinical trials and the anti-infection activity of B. clausii is gut microbiota dependent (10). Faecalibacterium prausnitzii ameliorated gut dysbiosis by increasing the abundance of short-chain fatty acids (SCFA)-producing bacteria (11). All these researches suggested that regulating the intestinal microbiota is an effective way of probiotics to protect the host.…”
Section: Introductionmentioning
confidence: 99%